Adaptive-Passive Virtual Inertia Control Based on Energy Balance Between a Synchronous Generator and a Three-Phase Inverter - Yazdani, Sara; Ferdowsi, Mehdi; Shamsi, Pourya (IEEE Energy Conversion Congress and Exposition, 2020)
The integration of renewable energy sources as grid-following units and taking part in having a major share in generation with no rotational inertia can lead to frequency instabilities. The concept of virtual inertia algorithm to maintain the stability of the power system by emulating a synchronous generator in the control structure has attracted attentions. However, a technique to quantify the virtual moment of inertia based on the stability requirements of the power system is still not available. Whereas, the passive maps in the interaction of a three-phase inverter with a synchronous generator in an isolated microgrid invokes the law of conservation of energy to solve the modeling problem. In this paper, a scheme of energy balance equation between a synchronous machine and a three phase inverter has been selected to give a quantifiable method to adaptively measure the virtual moment of inertial as a control parameter. The validation of the proposed method has been verified through the implementation of the control structure in a Hardware-in-the-Loop testbench in different scenarios.